Komunikasi Orang Tua dalam Resiliensi Keluarga dengan Anak Disabilitas Tunarungu Wicara di SLB As-Syafi'iyah Jakarta Timur - Rifa Dwi Poetri; Dini Wahdiyati; Farida Haryati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to analyze resilience communication within families with children with speech and hearing disabilities at SLB As-Syafi’iyah Jakarta Timur. The results show that open, adaptive, and collaborative communication is the main key in building family resilience, and highlight the importance of synergy between families, schools, and communities in creating an inclusive environment that supports the optimal development of children. Active family involvement in assistance, acceptance, and social support has been proven to strengthen the family’s psychological resilience in facing stigma and social challenges. This research uses a qualitative approach with a case study method, through in-depth interviews, observation, and documentation with parents of children with speech and hearing disabilities at the school. The findings identify five main processes of family resilience communication: creating new normality, affirming family identity, maintaining communication networks, utilizing internal and external resources, and maintaining a positive perspective. The conclusion emphasizes that reflective communication and cross-environment collaboration are essential foundations in building family resilience with children with speech and hearing disabilities.